MEASUREMENT OF VIBRATION LEVELS AND GEOMETRIC QUALITY OF RECONDITIONED LATHE PRODUCTS WITH VARIATIONS IN BASIC MACHINING ELEMENTS - Hendra Hendra; Admon Dani; Dedi Suryadi; Hernadewita Hernadewita (Asian Journal of Social and Humanities, 2023)
Machining parameters are something that must be considered, where machining parameters are related to vibrations (chatters) that occur during the cutting process. Vibration (chatter) can affect the quality of the geometry of the resulting product. To find out this, it is necessary to test the influence of machining parameters on the vibration level and quality of product geometry. Measurement of vibration level values and product geometry quality is carried out at variations of 60 rpm, 215 rpm, 330 rpm and 1140 rpm, with variations in cutting depth of 0.5 mm, 1 mm, 2 mm and 3 mm. The results of the cutting process with the influence of machining parameters (spindle rotation and cutting depth) on vibration, the most optimal value with a low vibration level is obtained, namely in the cutting process with spindle rotation parameters (n) 1140 rpm, and cutting depth (a) 1 mm produces a vibration value of 2.1 mm / s. However, for the most optimal cutting process, the highest vibration level value is produced, that is, in the cutting process with spindle rotation parameters (n) 215 rpm and cutting depth (a) 3 mm resulting in a vibration value of 3.4 mm / s. From the results of measuring the vibration level, it is obtained that the vibration level value has exceeded the permissible tolerance limit. However, for the influence of machining parameters on the quality of product geometry, results are obtained with the quality of product geometry that is still within the permissible tolerance limits, namely at spindle rotation (n) 1140 rpm. For the results of measuring the quality of product geometry at spindle rotation (n) 60 rpm, 215 rpm and 330 rpm, the quality results of product geometry obtained have exceeded the permissible tolerance limit.